2017
DOI: 10.1002/biof.1352
|View full text |Cite
|
Sign up to set email alerts
|

Differentially expressed haptoglobin as a potential biomarker for type 2 diabetic mellitus in Hispanic population

Abstract: Glycosylated hemoglobin (HbA1c) measurement is currently a primary tool for diagnosis of type 2 diabetes mellitus (T2DM), especially for the assessment of chronic hyperglycemia. However, many studies reported the limitation of using HbA1c for T2DM diagnosis/prognosis, such as poor sensitivities, difficult standardization, and variable cut points across ethnic groups. Therefore, the aim of this study was to discover novel biomarkers associated with elevated HbA1c levels as complementary T2DM diagnostic tools. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 52 publications
(68 reference statements)
0
5
0
Order By: Relevance
“…It follows that haptoglobin 2 alleles have a higher risk of developing the disease. The studies of Spanish or Chinese population have led to similar conclusions [50,51]. They also showed that inherited factor such as the phenotype of haptoglobin may play an important role in the pathogenesis of type 2 diabetes.…”
Section: Discussionmentioning
confidence: 71%
“…It follows that haptoglobin 2 alleles have a higher risk of developing the disease. The studies of Spanish or Chinese population have led to similar conclusions [50,51]. They also showed that inherited factor such as the phenotype of haptoglobin may play an important role in the pathogenesis of type 2 diabetes.…”
Section: Discussionmentioning
confidence: 71%
“…Interestingly, haptoglobin (Hp) was more abundant in diabetic groups with poor glycemic control. Pooled serum samples from Hispanic T2DM subjects with HbA 1c ≥ 53 mmol/mol showed 1.5-fold higher Hp than those with HbA 1c < 53 mmol/mol [22]. In addition, diabetic patients with retinopathy increased plasma Hp more than 1.5-fold than those without retinopathy [11].…”
Section: Discussionmentioning
confidence: 87%
“…36 A recent study done in Hispanics shows that subjects with the Hp2 allele may have a higher risk for the occurrence of T2DM. 37 As such, the current data show conflicting results and the association of the Hp genotypes with diabetes mellitus remains undetermined. In one Japanese cross-sectional analysis of >300 patients, an association was seen for fatty liver disease and non-alcoholic fatty liver disease in Hp2 carriers and this was associated with ferritin concentrations.…”
Section: Introductionmentioning
confidence: 84%